Crisis Of Authority In Islamic Educational Institutions: Strategic Response Of Islamic Education Management To The Shift In Generation Z's Trust In The Digital Era - Isrun Abdurahman; Rohman Pranoto; Agus Salim; Rizaldy Alpiansyah; Irfan Alkhotiri (Sekolah Tinggi Agama Islam Minhajul Haq, 2026)
The dynamics of Islamic education in the 21st century are facing disruptions triggered by technological innovations and the demographic shift of Generation Z. This article analyzes the phenomenon of the crisis of religious authority in Islamic educational institutions, where students (Gen Z) tend to trust religious content creators on social media (faithfluencers) more than their formal educators or kyai (traditional Islamic scholars). Using a descriptive qualitative approach based on library research, this study investigates the sociological and psychological roots of this trust shift, including the impact of parasocial interactions and the dominance of algorithmic authority. The results indicate that this crisis is also exacerbated by managerial bureaucratization within pesantren (Islamic boarding schools) and madrasas, which erodes charismatic authority. As a solution, Islamic Education Management (MPI) needs to formulate a crisis management framework based on Islamic values. The proposed tactical strategies include the hybridization of authority through the digitalization of sanad (chain of transmission) and adab (ethics), rebranding teacher competencies through creative content production training, the implementation of digital-based public relations strategies, and the integration of digital literacy into the curriculum. In conclusion, Islamic educational institutions must recalibrate themselves into digitally adaptive institutions without sacrificing the values of khidmah (sincere service) and pesantren traditions, in order to fortify the faith of Generation Z in the cyber ecosystem.